2020
DOI: 10.1038/s41598-020-58406-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of two conserved G-quadruplex forming motifs in the Nipah virus genome and their interaction with G-quadruplex specific ligands

Abstract: The G-quadruplex (GQ) motifs are considered as potential drug-target sites for several human pathogenic viruses such as Zika, Hepatitis, Ebola, and Human Herpesviruses. The recent outbreaks of Nipah virus (NiV) in India, the highly fatal emerging zoonotic virus is a potential threat to global health security as no anti-viral drug or vaccine in currently available. Therefore, here in the present study, we sought to assess the ability of the putative G-quadruplex forming sequences in the NiV genome to form G-qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 59 publications
(68 reference statements)
3
30
0
Order By: Relevance
“…The translation of some SARS-CoV-2 proteins requires the involvement of human ribosomes; thus, it is possible to repress the translation of SARS-CoV-2 proteins via stabilizing the G-quadruplex structures. In fact, this inhibition effect has been reported in some other viral studies [67,71]. The negative-sense strand serves as templates for the synthesis of the positive-sense strand and the sub-genomic RNAs.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The translation of some SARS-CoV-2 proteins requires the involvement of human ribosomes; thus, it is possible to repress the translation of SARS-CoV-2 proteins via stabilizing the G-quadruplex structures. In fact, this inhibition effect has been reported in some other viral studies [67,71]. The negative-sense strand serves as templates for the synthesis of the positive-sense strand and the sub-genomic RNAs.…”
Section: Discussionsupporting
confidence: 52%
“…However, it is well-acknowledged that the RNA Gquadruplexes is more stable than their DNA counterparts [65,66] and SARS-CoV-2 is a single-strand RNA virus, which may be conducive to its structure formation. Several emerging studies have demonstrated the formation of two-quartet G-quadruplexes in viral sequences, which could serve as antiviral elements under the presence of G-quadruplex ligands [53,67,68]. Moreover, the K + (potassium ion), one of the primary positive ions inside human cells, can strongly support the formation of G-quadruplexes.…”
Section: Discussionmentioning
confidence: 99%
“…The G4 binders TMPyP4, ex-NDI 2, and BRACO-19 are reported to inhibit bacterial growth and virulence via a G4-mediated mechanism ( Perrone et al, 2017 ; Mishra et al, 2019a , b ). Conserved G-rich regions in the Zika virus ( Fleming et al, 2016 ), Herpes Simplex virus ( Artusi et al, 2015 ), Nipah ( Majee et al, 2020a ), Adenovirus ( Majee et al, 2020b ), and other viruses have also been shown to form G4 conformations and are proposed as anti-viral drug targets ( Ruggiero and Richter, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis revealed the presence of GQ motifs in various genes of Klebsiella pneumoniae that influenced the gene expression (Shankar et al, 2020). Likewise, several human infecting viruses including Zika (Fleming et al, 2016), Nipah (Majee et al, 2020a), Herpes Simplex virus (Biswas et al, 2016), Human Papillomavirus (TlučkovĂĄ et al, 2013), and Human Adenovirus (Majee et al, 2020b) are reported to possess potential GQ forming sequences. G-quadruplex sequences in the L gene of Ebola virus and the FIGURE 1 | G-quadruplex topologies and GQ in Vibrio cholerae reference genome.…”
Section: Introductionmentioning
confidence: 99%